Flexible and transparent supercapacitor based on In2O3 nanowire/carbon nanotube heterogeneous films - Chen, Po-Chiang; Shen, Guozhen; Sukcharoenchoke, Saowalak; Zhou, Chongwu (Applied physics letters, 2009)
In this paper, a supercapacitor with the features of optical transparency and mechanical flexibility has been fabricated using metal oxide nanowire/carbon nanotube heterogeneous film, and studies found that the power density can reach 7.48 kW/kg after galvanostatic measurements. In addition, to study the stability of flexible and transparent supercapacitor, the device was examined for a large number of cycles and showed a good retention of capacity (∼88%). This approach could work as the platform for future transparent and flexible nanoelectronics.